Why She Must Lead (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
Gender bias and color bias has always been a  critical social evil in degrading humanity and  equality. It has lead to social injustice and  curbing of creativity and talent of masses. The  creative and hardworking skilled women of color  are not acknowledged and appreciated for their  work which develops resentment and anger  amongst themselves in many countries. Since,  diversity is the soil of our mother Earth; we must  stand together for an empowered future.
Keywords: Gender; degrading; hardworking